PUBLIC ADVOCACY AS A MEDIATOR AND A REFEREE ON ENVIRONMENTAL ISSUES (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Faced with the crisis of slowness that passes the Judiciary, we must think of new ways to solve social conflicts without always resorting to justice. Especially those more sensitive demands, such as those that protect environmental law, where delay in solving problems can cause irreversible damage to both the environment and those who depend on it economically, those most excluded. Given this, the Public Defender to act as mediator or arbitrator in environmental matters involving communities or even people in need and the cause of environmental damage, which in this case may be a company, a public service concessionaire, or even the State itself. Such action could bring benefits to both the environment and those involved in the conflict in the face of speed and greater efficiency in the resolution of the litigation. The method of approach to be used is the analytic-deductive, so that the object of study is visualized as resulting from multiple determinations and factors, especially of a historical and constitutional order. The extraction of the true contents of legal institutes is satisfactory with their inquiry from the analytic-deductive point of view.